Renal metastasis of gastric cancer caused acute kidney injury which resulted with hemodialysis: case report and literature review - Dilber, Ivo; Pleština, Stjepko; Kekez, Domina; Šokec, Ivana Vukovac; Ćorić, Marijana; Prejac, Juraj (Frontiers in Oncology, 2024)
Gastric cancer ranks fourth among the most commonly diagnosed cancers, with over a million new cases diagnosed worldwide each year. Acute and chronic kidney damage are common in patients with malignant diseases and are associated with increased risk of complications and mortality. Rarely, acute renal insufficiency may result from bilateral infiltration of renal parenchyma by tumor cells from another organ. We present a case of a patient with clinical suspected gastric cancer and metastases to the kidneys leading to acute renal failure requiring hemodialysis. Despite gastric biopsies, no tumor cells were found, while histopathological examination of enlarged intra-abdominal lymph node biopsy material confirmed adenocarcinoma of signet ring cell originating from the digestive system. Stomach cancer was identified as the most likely primary site after the kidney biopsy was performed. To the best of our knowledge, no case of gastric cancer leading to kidney metastases and acute renal failure requiring renal replacement therapy was yet described. Multidisciplinary collaboration among oncologists, urologists, radiologists, pathologists, and nephrologists is essential for the optimal treatment outcome of these patients, who generally have a poor prognosis.